A Guide for the Design of Functional Polyaromatic Organophosphorus Materials. Issue 56 (27th July 2017) - Hindenberg, Philip; López‐Andarias, Alicia; Rominger, Frank; de Cózar, Abel; Romero‐Nieto, Carlos
Abstract: The impact of integrating six‐membered phosphorus heterocycles into a poly(hetero)aromatic materials is investigated. Mechanistic studies reveal the key synthetic requirements to embed the latter phosphorus heterocycles in polyaromatic molecules. DFT calculations indicate that introducing six‐membered phosphorus rings into π‐extended molecules induces a particular electron distribution over the π‐extended system. Electrochemical investigations confirm that inserting six‐membered phosphacycles into polyaromatics triggers ambipolar redox behavior. Steady‐state spectroscopy reveals that fusing pyrroles with phosphorus‐containing polyaromatic molecules induces fluorescence quantum yields as high as 0.8, whereas transient absorption spectroscopy demonstrates that fusing thiophenes promote the formation of non‐emissive triplet‐excited states. As a whole, the optoelectronic properties of fused phosphorus‐containing materials give rise to promising performances in photoelectrochemical cells. Moreover, X‐ray analyses confirm that the 3D arrangement in the solid state of polyaromatic systems containing six‐membered phosphorus rings can be tailored through post‐functionalization of the phosphorus center. Altogether, this investigation sets the bedrock for the design of a new generation of highly functional polyaromatic organophosphorus materials, keeping control over their electrochemical properties, fluorescence features, photo‐induced excited states, and 3D molecular arrangement. Abstract : Tracing the lines : Detailed investigations on a series of polycyclic organophosphorus materials containing six‐membered phosphorus heterocycles reveal the key parameters for the synthesis of functional architectures with different electrochemical behaviors, fluorescence quantum yields up to 0.8, and versatile means to keep control over the nature of the photo‐induced excited states and the 3D molecular arrangement in the solid state.